Proton pump inhibitors and subacute cutaneous lupus erythematosus: an under‐recognized phenomenon?. (February 2014) - Cookson, H.; Walsh, S.
<x xml:space="preserve">Abstract</x> ORIGINAL ARTICLE, p 342